Factors Causing Drug Abuse in Rehabilitation Clients and Psychological Attendants - Yolita, Enggly; Tasadi, Rafsel; Desmita, Desmita; Z, Sri Putri Rahayu (Darussalam: Journal of Psychology and Educational, 2022)
The dominant problem encountered is the rampant use of drugs in Payakumbuh City which makes the causative factor dari drug abuse rehabilitation. Seeing the increasing number of drug use in Indonesia, there is also more damage to the younger generation in Indonesia. The purpose of this study was to determine the factors causing drug abuse in rehabilitation clients in BNN Payakumbuh City. This research is descriptive qualitative research. The data collection was carried out by interviewing subjects totaling 4 victims of drug abuse who were undergoing rehabilitation. Based on the results of the study, it was found that the factors causing the actions of drug abusers in the National Narcotics Agency (BNN) of Payakumbuh City were individual and environmental factors (peers). The individual factor comes from having curiosity and wanting to try drugs. From family, factors do not affect the rehabilitation client on the cause of drug abuse in the rehabilitation client in BNN Payakumbuh City. Environmental factors influence on the rehabilitation client on the causes of drug abuse. Environmental factors (peers) found that the client was in drug abuse from his peers' problems which started from introducing drugs to informants as well as inviting informants to use drugs while gathering together. Meanwhile, from the information media factor, it was found that 2 clients did not get information about drugs from the information media but 2 rehabilitation clients got news about drugs while also looking for information about drugs in the information media but did not affect the client on the cause of drug abuse in rehabilitation clients in BNN Payakumbuh City